PENGGUNAAN MODEL PROBLEM BASED LEARNING TERHADAP PENINGKATAN PENGUASAAN KONSEP SISWA KELAS XI SMK PADA MATERI FLUIDA STATIS - Sudirman Sudirman (Universitas Sultan Ageng Tirtayasa, 2015)
The advanced Research goal is to Obtain a picture of the use of models to enhance problem-based learning concept mastery of vocational students in class XI and the static fluid material to Obtain a picture of students' responses to the model of problem based learning. The method used is a quasi-experimental design